Optimum condition for rearing giant freshwater prawn (Macrobrachium rosenbergii) Post Larvae - Nora Azreena Ismail (2015)
Understanding Macrobrachium rosenbergii optimum condition and performance in aquaculture is important to optimize the design, management of tanks, and other culture conditions. The objective of this study is to study the optimum condition for rearing Macrobrachium rosenbergii post larvae (PL). An experiment was conducted for 28 days to determine the effects of stocking density of 80 PL, 70 PL and 60 PL per half liter per tank with the present of black nylon netting as substrate and effects of present of substrate, present of blue colouring and control with 60 PL per half liter per tank. Data collected are based on the PL growth performance of body weight and total body length and survival percentage. Result indicated that for the stocking density, M. rosenbergii PL reared in 60 PL stocking density had better growth performance of weight gain of 0.0775 ± 0.0132g and length gain 11.0 ± 1.88mm and survival percentage of 77.760 ± 7.85%. Lastly by 80 PL (substrate) with weight gain of 0.0595 ± 0.0185g and length gain of 9.2 ± 1.58mm and survival percentage of 72.064 ± 10.64%. For the substrate and coloring, the best growth performance was obtained by 60 PL (substrate) with weight gain of 0.0775 ± 0.0132g and length gain of 11.0 ± 1.88mm. The least growth performance was recorded by 60 PL (coloring) with 0.0572± 0.0098g and 9.7± 1.70mm. In contrast in the growth performance, the best survival percentage was obtained by 60 PL (coloring) with 88.500 ± 3.78%, followed by the 60 PL (control) and the least survival percentage was recorded by 60 PL (substrate) with 77.760 ± 7.85%. In conclusion, the best growth performance and survival percentage for stocking density tested is 60 PL (Substrate). Among substrate and coloring treatments, the best growth performance showed by 60 PL (substrate) while best survival percentage showed by 60 PL (coloring). The present of substrate and coloring in rearing M. rosenbergii can be considered as optimum condition provided maintenance. Present of coloring is suitable to increase survival percentage for short period of time such as during transportation instead of long-term rearing. Hence, it gives high survival percentage but did not perform in growth in rearing period.